Population Circulation and the Transformation of Ancient Zuni Communities - Schachner, Gregson, 1974- (Book collections on Project MUSE., 2012)
Schachner analyzes a population shift in the Zuni region of west-central New Mexico during the thirteenth century AD that led to the inception of major demographic changes, the founding of numerous settlements in frontier zones and the initiation of radical transformations of community organization.